2020
DOI: 10.32493/frkm.v3i3.3588
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Prestasi Belajar Mahasiswa Tingkat 1 Universitas Pamulang Fakultas Ekonomi Program Studi Manajemen Reguler A.

Abstract: Pendidikan pada hakekatnya bertujuan untuk membentuk sumber daya manusia seutuhnya yang berkualitas. Kualitas pendidikan erat kaitannya dengan proses pembelajaran karena proses pembelajaran merupakan salah satu segi terpenting dalam bidang pendidikan. Selain adanya anggapan tersebut prestasi belajar mahasiswa juga dipengaruhi faktor-faktor lain.Metode yang digunakan dalam penelitian ini kuantitatif. Data diambil dari hasil kuesioner. Analisis data dilakukan dengan mengunakan 4 (empat) tahapan yaitu pengumpulan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…According to the findings of the lesson, instructors of Christian religious education courses require extensive training in order to generate scientific compositions that will increase the quality of their students' learning and help them advance in their careers. A crucial step is to ensure that the training is a need for instructors and schools, rather than a frivolous pastime (Hilmi, 2013;Qurbani, 2017). This identification is in line with previous study who believes that before doing training, it is necessary to identify training requirements inside the company in order to achieve the intended outcomes (Firdousi, 2011).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…According to the findings of the lesson, instructors of Christian religious education courses require extensive training in order to generate scientific compositions that will increase the quality of their students' learning and help them advance in their careers. A crucial step is to ensure that the training is a need for instructors and schools, rather than a frivolous pastime (Hilmi, 2013;Qurbani, 2017). This identification is in line with previous study who believes that before doing training, it is necessary to identify training requirements inside the company in order to achieve the intended outcomes (Firdousi, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…Other researchers also found that the most effective forms of professional development were those based in schools and related to the daily activities of teachers and students (Ganser, 2015). Teachers need to experience the process of learning, collaboration, and application to the activities they are currently engaged in, accompanied by school and classroom-based environmental support, to be able to incorporate new behaviors into teacher teaching practices (Danim, 2012;Qurbani, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve the learning objectives in the Biology Learning 10.31932/jpbio.v8i1. 2307 Fajar & Suryani jurnaljpbio@gmail.com Evaluation course, the mandate of the lecturer in charge of the course must be able to function as a motivator and facilitator for students to develop their potential optimally by utilizing all available learning facilities and a conducive learning system (Qurbani, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Achievement path students are expected to make achievements like in school. Students with achievements have trained talents because achievements are obtained from programmed efforts (Kim et al, 2020;Qurbani et al, 2020;Retnowati et al, 2016). Students with achievements are important skills for prospective teachers because they can inspire and motivate students.…”
Section: Introductionmentioning
confidence: 99%